2022
DOI: 10.3390/antiox11122387
|View full text |Cite
|
Sign up to set email alerts
|

New Treatment for the Cognitive and Emotional Deficits Linked with Paclitaxel-Induced Peripheral Neuropathy in Mice

Abstract: Chemotherapy-provoked peripheral neuropathy and its linked comorbidities severely reduce the quality of a patient’s life. Its therapy is not completely resolved and has become an important clinical challenge. The protective actions of molecular hydrogen (H2) in many neurological disorders have been described, but its effects on memory and the emotional deficits accompanying neuropathic pain induced by chemotherapy remain unknown. In this study, using male mice injected with paclitaxel (PTX), we examined the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…In line with this, our results demonstrated increased levels of the inflammasome NLRP3 and the oxidative marker 4-HNE, accompanied by the decreased expression of HO-1 and SOD-1 in the DRG of CIS-injected male and female mice. Treatment with HRW normalized these inflammatory and oxidative reactions caused by CIS in the DRG, revealing the potent anti-inflammatory and antioxidant actions of this treatment, as previously demonstrated in paclitaxel-injected mice [37]. H 2 inhibited the neuropathic pain caused by nerve lesions by reversing the overexpression of proinflammatory cytokines and 4-HNE [58].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In line with this, our results demonstrated increased levels of the inflammasome NLRP3 and the oxidative marker 4-HNE, accompanied by the decreased expression of HO-1 and SOD-1 in the DRG of CIS-injected male and female mice. Treatment with HRW normalized these inflammatory and oxidative reactions caused by CIS in the DRG, revealing the potent anti-inflammatory and antioxidant actions of this treatment, as previously demonstrated in paclitaxel-injected mice [37]. H 2 inhibited the neuropathic pain caused by nerve lesions by reversing the overexpression of proinflammatory cytokines and 4-HNE [58].…”
Section: Discussionsupporting
confidence: 71%
“…Molecular hydrogen (H 2 ) produces strong anti-inflammatory and antioxidant actions that are predominantly attributed to its capacity to inhibit the synthesis of NF-κB and the subsequent release of pro-inflammatory factors [34,35], as well as by reducing ROS levels and increasing the expression of antioxidant enzymes such as SOD-1 and HO-1 [36]. Recent experiments further revealed that the therapeutic administration of hydrogen-rich water (HRW) has beneficial effects in animals with paclitaxel-induced neuropathic pain [37]. This treatment also reduced the nociceptive and emotive disturbances occasioned by nerve injury and persistent paw inflammation in male mice [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients adopt PCER to reassess the impact of trauma and analyse the reason for trauma. This can form a positive feedback mechanism between SOC and PCER 54. However, positive coping styles and SOC are not always helpful in alleviating trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical rodent models provide an important tool for advancing our understanding of the mechanisms underlying cognitive dysfunction during chronic pain states and other neurological disorders. Previous work shows these conditions can result in disease-induced negative affect 12 and deficits in motivated behavior, reflecting comorbidities observed in clinical populations 13,14 . However, using preclinical models to reliably capture clinical symptoms faces numerous experimental challenges.…”
Section: Introductionmentioning
confidence: 98%
“…Morris Water Maze 19,20 , Barnes Maze 16 ) and recognition tasks (e.g. novel object recognition [21][22][23] ) have been implemented to measure cognitive function in large cohorts of mice 12,[24][25][26][27][28] , including chemically-induced rodent pain models such as Chemotherapy Induced Peripheral Neuropathy [29][30][31] and Complete Freund's Adjuvant 32 which exhibit a limited period of pain sensitivity. However, these paradigms rely on hippocampalbased spatial memory and the HPA-driven stress-influenced motivated behavior that provide an experimental challenge for evaluating executive function and other subdomains of cognitive behavior.…”
Section: Introductionmentioning
confidence: 99%